Genetic regulation of IL1RL1 methylation and IL1RL1-a protein levels in asthma. Issue 3 (8th March 2018) - Dijk, F. Nicole; Xu, Chengjian; Melén, Erik; Carsin, Anne-Elie; Kumar, Asish; Nolte, Ilja M.; Gruzieva, Olena; Pershagen, Goran; Grotenboer, Neomi S.; Savenije, Olga E.M.; Antó, Josep Maria; Lavi, Iris; et al.
Interleukin-1 receptor–like 1 ( IL1RL1 ) is an important asthma gene. (Epi)genetic regulation of IL1RL1 protein expression has not been established. We assessed the association between IL1RL1 single nucleotide polymorphisms (SNPs), IL1RL1 methylation and serum IL1RL1-a protein levels, and aimed to identify causal pathways in asthma. Associations of IL1RL1 SNPs with asthma were determined in the Dutch Asthma Genome-wide Association Study cohort and three European birth cohorts, BAMSE (Children/Barn, Allergy, Milieu, Stockholm, an Epidemiological survey), INMA (Infancia y Medio Ambiente) and PIAMA (Prevention and Incidence of Asthma and Mite Allergy), participating in the Mechanisms of the Development of Allergy study. We performed blood DNA IL1RL1 methylation quantitative trait locus (QTL) analysis (n=496) and (epi)genome-wide protein QTL analysis on serum IL1RL1-a levels (n=1462). We investigated the association of IL1RL1 CpG methylation with asthma (n=632) and IL1RL1-a levels (n=548), with subsequent causal inference testing. Finally, we determined the association of IL1RL1-a levels with asthma and its clinical characteristics (n=1101). IL1RL1 asthma-risk SNPs strongly associated with IL1RL1 methylation (rs1420101; p=3.7×10 −16 ) and serum IL1RL1-a levels (p=2.8×10 −56 ). IL1RL1 methylation was not associated with asthma or IL1RL1-a levels. IL1RL1-a levels negatively correlated with blood eosinophil counts, whereas there was no association between IL1RL1-a levels and asthma. In conclusion, asthma-associated IL1RL1 SNPs strongly regulate IL1RL1 methylation and serum IL1RL1-a levels, yet neither these IL1RL1- methylation CpG sites nor IL1RL1-a levels are associated with asthma. Interleukin-1 receptor-like 1 ( IL1RL1 ) SNPs regulate IL1RL1 -methylation and serum IL1RL1-a levels, yet these effects are not related to asthma http://ow.ly/AStC30hSvGy